Fiscal implications of the Federal Reserve's balance sheet normalization - Michele Cavallo; Marco Del Negro; W. Scott Frame; Jamie Grasing; Benjamin A. Malin; Carlo Rosa (Federal Reserve Bank of New York, 2018)
The paper surveys the recent literature on the fiscal implications of central bank balance sheets, with a special focus on political economy issues. It then presents the results of simulations that describe the effects of different scenarios for the Federal Reserve's longer-run balance sheet on its earnings remittances to the U.S. Treasury and, more broadly, on the government's overall fiscal position. We find that reducing longer-run reserve balances from 2.3 trillion (roughly the current amount) to 1 trillion reduces the likelihood of posting a quarterly net loss in the future from 30 percent to under 5 percent. Further reducing longer-run reserve balances from 1 trillion to pre-crisis levels has little effect on the likelihood of net losses.
Keywords: E58; E59; E69; 330; central bank balance sheets; monetary policy; remittances; Zentralbank; Bankrechnungslegung; Bilanzpolitik; Geldpolitik; Gewinnverwendung; USA